ANALISIS NILAI TAMBAH DAN GAMBARAN BUSINESS MODEL CANVAS AGROINDUSTRI KERIPIK TEMPE SAGU (STUDI KASUS PADA UD. SAFNUR KABUPATEN BANJARNEGARA) - Sarno, Sarno -; Solekan, Muhamad; Kinding, Dwi Putriana Nuramanah; Pujiyanto, M. Aris; Prabowo, Rossi (MEDIAGRO, 2024)
UD. Safnur is one of the agro-industries that focus on processing tempe sago chips in Banjarnegara Regency. The problems faced are limited technology, labor shortages, marketing, and the strategies and business models used do not have clear directions and goals. The research aims to determine the added value and determine the business model canvas of sago tempeh chips agro-industry UD. Safnur. The basic research methods used are case study method, descriptive method, and Participatory Action Research method. The data used in this research consisted of primary data and secondary data, both qualitative and quantitative. The data analysis used in this research is the value-added analysis of Hayami method and business model canvas analysis. Based on the results of the study, it shows that the sago tempeh chips agro-industry at UD. Safnur produces added value of Rp 59,000/kg. The value-added ratio is 59 percent of the product value, which means that the processing of sago tempeh chips provides high added value. The description of UD Business Model Canvas. Safnur includes Customer Segments ranging from children to parents or all circles, healthy snack consumers and resellers, Value Proposition offered quality raw materials, healthy because it is not made from MSG, easy to obtain, while for Channels includes a direct sales system and through resellers. Customer Relationship that is prioritized is to provide excellent and professional customer service. Key Activities include production and marketing of tempe sago chips. Key Resources include human resources, physical resources, and intellectual resources. Key Partnerships involve soybean and sago traders and resellers. Cost Structure includes fixed costs and variable costs, while Revenue Streams are income from the sale of tempe sago chips.